Cost Effectiveness and Resource Allocation - Rovira, Joan; Youngkong, Sitaporn
Cost Effectiveness and Resource Allocation considers manuscripts on all aspects of cost-effectiveness analysis, including conceptual or methodological work, economic evaluations, and policy analysis related to resource allocation at a national or international level.